Monoclonal antibodies to rat renal antigens. - Shimizu, F (1984)
We have developed hybridoma cell lines which secrete monoclonal antibodies to some rat renal antigens, namely the brush border of proximal tubular epithelium and the cytoplasm of tubular cells. The immunoglobulin class of the hybridoma was found to be IgG1. Specific antibody activity against either glomerular basement membrane (GBM) and tubular basement membrane (TBM) or Bowman's capsule and a part of TBM was observed, although these hybridoma cell lines have not yet been successfully established. In particular, the hybridoma secreting antibodies to TBM did not remain stable during antibody production, and was lost during the culture and cloning procedures. These monoclonal antibodies should be of value in research on the pathogenesis of human glomerulonephritis.